1996
DOI: 10.1242/jcs.109.4.787
|View full text |Cite
|
Sign up to set email alerts
|

Partial colocalization of glucocorticoid and mineralocorticoid receptors in discrete compartments in nuclei of rat hippocampus neurons

Abstract: The glucocorticoid receptor and the mineralocorticoid receptor are hormone-dependent transcription factors. They regulate the excitability of rat hippocampus CA1 neurons in a coordinated fashion. We studied the spatial distribution of these transcription factors in nuclei of CA1 neurons by dual labeling immunocytochemistry and confocal microscopy, combined with novel image restoration and image analysis techniques. We found that both receptors are concentrated in about one thousand clusters within the nucleus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(54 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…The results showed that Manders' coefficients had a higher overlap of S1R on AQP (M2): 0.458 ± 0.046 (AQP8) > 0.411 ± 0.04 (AQP3) > 0.307 ± 0.109 (AQP11) (Figure 8D-F). The cross-correlation analysis [52] showed bell-shaped curves (Figure S2) with the following CCF maxima values: 0.562 ± 0.129 (AQP11) > 0.453 ± 0.212 (AQP3) > 0.355 ± 0.021 (AQP8) (Figure 8D-F). Taken together, the results suggest at least a partial colocalization of S1R and AQPs, confirming that the herein used cellular model is suitable for studying the effect of S1R modulators on AQP-mediated antioxidant effect.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results showed that Manders' coefficients had a higher overlap of S1R on AQP (M2): 0.458 ± 0.046 (AQP8) > 0.411 ± 0.04 (AQP3) > 0.307 ± 0.109 (AQP11) (Figure 8D-F). The cross-correlation analysis [52] showed bell-shaped curves (Figure S2) with the following CCF maxima values: 0.562 ± 0.129 (AQP11) > 0.453 ± 0.212 (AQP3) > 0.355 ± 0.021 (AQP8) (Figure 8D-F). Taken together, the results suggest at least a partial colocalization of S1R and AQPs, confirming that the herein used cellular model is suitable for studying the effect of S1R modulators on AQP-mediated antioxidant effect.…”
Section: Resultsmentioning
confidence: 98%
“…To evaluate the colocalization, we used JACoP (just another Colocalization Plugin) from Fiji to quantify the Pearson's correlation coefficient r, Manders' colocalization coefficient (M1 and M2) and Van Steensel's Cross-correlation Function (CCF) of 3D images [50][51][52].…”
Section: Immunofluorescence Staining Confocal Microscopy and Colocalization Analysismentioning
confidence: 99%
“…5 , first column, merged image and line profile). To quantitatively evaluate the colocalization, we employed a cross-correlation function (CCF) analysis, which measures Pearson’s correlations by shifting the image of one fluorescence channel to the x-direction ( van Steensel et al, 1996 ; Fig. 5 , bottom row).…”
Section: Resultsmentioning
confidence: 99%
“…IRIF size was measured with a 2D Crosscorrelation plugin for ImageJ as described by Reindl et al 16 . It is based on the approach introduced by Van Steensel et al 45 using the Pearson correlation coefficient with the gray values for the i-th pixel in image A and image B, respectively, and the respective mean gray values. For size measurement, image B is a duplicate of image A, and the cross-correlation function is called the autocorrelation function (ACF).…”
Section: Methodsmentioning
confidence: 99%